1991
DOI: 10.1515/mamm.1991.55.3.339
|View full text |Cite
|
Sign up to set email alerts
|

Habitat selection in population of cricetine rodents in the region Delta (Argentina)

Abstract: We employed a live trapping grid to analyse the effect of heterogeneity habitat on dispersion of Akodon azarae, Oxymycterus rutilans and Oryzomys delticola. The reproduction and survival of three species are associated with their residency in the grassland, avoided the use of woodland. A. azarae reproductive and non-reproductive individuals preferentially use the sites dominated by Ambrosia scabra (microhabitat 1). Their residency at those sites would present nutritional advantages due to higher availability o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 20 publications
1
26
0
Order By: Relevance
“…However, O. rufus is not dependent on the floristic composition of the microhabitats, because it uses sites dominated by grass (eg C. selloana) or shrubs (eg B. spicata). Bonaventura et al (1991) observed that reproductive individuals of O. rufus were not associated with the foliage availability. Considering O. rufus is mainly an insectivorous rodent (Barlow 1969, Kravetz 1972, Dalby 1975, the use of the microhabitats 1, 2, and 3 is likely to be due to the fact that such sites are more favorable for feeding on account of the greater availability of arthropods (Fig.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…However, O. rufus is not dependent on the floristic composition of the microhabitats, because it uses sites dominated by grass (eg C. selloana) or shrubs (eg B. spicata). Bonaventura et al (1991) observed that reproductive individuals of O. rufus were not associated with the foliage availability. Considering O. rufus is mainly an insectivorous rodent (Barlow 1969, Kravetz 1972, Dalby 1975, the use of the microhabitats 1, 2, and 3 is likely to be due to the fact that such sites are more favorable for feeding on account of the greater availability of arthropods (Fig.…”
Section: Discussionmentioning
confidence: 89%
“…In the delta of the Paraná River Bonaventura et al (1991) have studied the spatial distribution of O. rufus, and they could not find factors influencing the habitat selection of this rodent which were related to objective measurements of the quality of such habitats.…”
Section: Introductionmentioning
confidence: 99%
“…Comparing presence/absence of ectoparasites associated with every host species in this study, A. azarae showed the least similarity with every other rodent species. In contrast with the remaining rodents, which are associated with aquatic microhabitats, A. azarae is mostly associated with grassland, where seeds are dominant (Bonaventura et al 1991). However, the remaining host rodents which have similar ecological and ethological characteristics, showed higher similarities in relation to their ectoparasite species and particularly H. brasiliensis and S. aquaticus, the most semiaquatic rodents (Massoia & Fornes 1964, Massoia 1976, showed the same five ectoparasite species, although all of them preferred the first host species.…”
Section: Resultsmentioning
confidence: 99%
“…This result suggests that particular characteristics and strategies of this rodent sex would influence its ectoparasite population. Studies on the home range size and overlapping of wild rodents show that the average distance traveled by males in the breeding season is greater than that traveled by females (Bonaventura et al 1990). Furthermore, interspecific competition limits the use of territory by females during the reproductive season (Dalby 1975).…”
Section: Discussionmentioning
confidence: 99%